Elevated uric acid level decreases glycated hemoglobin in type 2 diabetes mellitus - Muhammad Fahmi Hidayat; Santi Syafril; Dharma Lindarto (Universa Medicina, 2014)
BackgroundType 2 diabetes mellitus is a heterogeneous disease which is characterized by variable degrees of insulin resistance and impaired insulin secretion. Uric acid has been identified as a marker for a number of metabolic and hemodynamic abnormalities. In diabetic patients, there is biochemical interaction between serum glucose and purine metabolism, with increased excretion of uric acid during hyperglycemia and glycosuria. The objective of this study was to evaluate the correlation of serum uric acid levels with glycated hemoglobin (HbA1c) and blood glucose levels in type 2 diabetes patients.MethodsA cross sectional study from May until July 2014 had been done in 82 type 2 diabetes patients. Serum was analyzed for uric acid, fasting and 2-hour post prandial blood glucose and lipid profile. Spearman correlation test was used to assess associations of HbA1c, fasting and post prandial blood glucose with serum uric acid levels.ResultsThere was a negative correlation of HbA1c with serum uric acid levels (r=-0.407; p=0.000) and of fasting and post prandial blood glucose with serum uric acid levels (r=-0.338; p=0.002 and r=-0.318; p=0.004, respectively).ConclusionsSerum uric acid level was associated with HbA1c, fasting and post prandial blood glucose suggesting a significant role of serum uric acid in the deterioration of glucose toleration.